2011
DOI: 10.1128/aem.02450-10
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Composition of Caseicins A and B as a Means of Determining the Contribution of Specific Residues to Antimicrobial Activity

Abstract: Caseicin A (IKHQGLPQE) and caseicin B (VLNENLLR) are antimicrobial peptides generated through the bacterial fermentation of sodium caseinate, and on the basis of this and previous studies, they are active against many Gram-negative pathogens (Cronobacter sakazakii, Cronobacter muytjensii, Salmonella enterica serovar Typhimurium, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas fluorescens) as well as the Gram-positive organism Staphylococcus aureus. Here we describe further studies with the aim of esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…Template-based studies of peptide derivatives obtained through manipulation of the amino acid sequence have often been performed in order to identify properties that are important for AMP activity (12). Such studies have shed light on the importance of specific amino acids and residue positions in the activities of different peptides (13)(14)(15). However, it appears that the effect of particular manipulations is context dependent and varies according to the template sequence, in that analogous substitutions may have substantially different effects on different peptides or at different positions in the primary sequence (16).…”
mentioning
confidence: 99%
“…Template-based studies of peptide derivatives obtained through manipulation of the amino acid sequence have often been performed in order to identify properties that are important for AMP activity (12). Such studies have shed light on the importance of specific amino acids and residue positions in the activities of different peptides (13)(14)(15). However, it appears that the effect of particular manipulations is context dependent and varies according to the template sequence, in that analogous substitutions may have substantially different effects on different peptides or at different positions in the primary sequence (16).…”
mentioning
confidence: 99%
“…That study revealed that the replacement of the C-terminal arginine of caseicin B with alanine resulted in a generally greatly reduced activity against Gram-negative targets, whereas activity against S. aureus was not affected (22). Indeed, the results indicated that the anti-Gram-positive activity of the peptides was less sensitive to change than their antiGram-negative properties (22). Notably, the previous study focused on only a selection of the residues within these peptides, and these variants differed from the wild-type peptides by no more than one amino acid.…”
mentioning
confidence: 99%
“…Milk-derived AMPs are of particular interest and have been investigated since the 1930s (11), resulting in the identification of a number of peptides which demonstrate activity against Gram-positive (14,19,29) or Gram-negative (9,17) pathogens. Two of the most noteworthy of the milk-derived AMPs are caseicins A (IKHQGLPQE) and B (VLNENLLR), which were identified following a bacterial fermentation of sodium caseinate (9) and have previously been found to be active against a range of pathogenic bacteria, such as Cronobacter sakazakii (9), Cronobacter muytjensii, Staphylococcus aureus, and Salmonella enterica serovar Typhimurium (22). The precise mechanism by which caseicins A and B act remains unclear, and thus, to gain more insight into the importance of specific residues within these peptides, eight synthetic variants were generated which differed subtly from their natural equivalents (22).…”
mentioning
confidence: 99%
See 2 more Smart Citations